Fusing Stretchable Sensing Technology with Machine Learning for Human–Machine Interfaces. (18th March 2021) - Wang, Ming; Wang, Ting; Luo, Yifei; He, Ke; Pan, Liang; Li, Zheng; Cui, Zequn; Liu, Zhihua; Tu, Jiaqi; Chen, Xiaodong
Abstract: Sensors and algorithms are two fundamental elements to construct intelligent systems. The recent progress in machine learning (ML) has produced great advancements in intelligent systems, owing to the powerful data analysis capability of ML algorithms. However, the performance of most systems is still hindered by sensing techniques that typically rely on rigid and bulky sensor devices, which cannot conform to irregularly curved and dynamic surfaces for high‐quality data acquisition. Skin‐like stretchable sensing technology with unique characteristics, such as high conformability, low modulus, and light weight, has been recently developed to solve this issue. Here, the recent progress in the fusion of emerging stretchable electronics and ML technology, for bioelectrical signal recognition, tactile perception, and multimodal integration is summarized, and the challenges and future developments are further discussed. These efforts aim to accelerate various perception and reasoning tasks for advanced intelligent applications, such as human–machine interfaces, healthcare, and robotics. Abstract : Fusing stretchable sensing technology with machine learning (ML) is expected to unlock novel opportunities in healthcare, extend human–machine interactions, and enhance the functionalities of prostheses and robots. Here, the recent progress, challenges, and prospects of stretchable sensing‐ML systems are discussed. It offers clues to fully take advantage of the two emerging technologies for future intelligent systems.